Kwandang waterfront city development study against the water conditions of north gorontalo regency - Djau, Bambang (Gorontalo State University, 2021)
Kwandang Waterfront City is a directive on urban development plans by Government Regency of North Gorontalo where there is a plan for coastal reclamation with beachfront conditions are dense settlements. However, it has not been stated in the Zoning Plan of Coastal Areas and Small Islands (RZWP3K) in Gorontalo Province. This paper aims to explore the feasibility of Kwandang Waterfront City development to changes in the physical condition of the aquatic environment of the North Gorontalo Regency through spatial analysis and weighting methods. The results of this paper can be taken into consideration in conducting a review of Coastal Spasial Plan, as a form of support for the Kwandang Waterfront City urban development plan.